(untitled) - Thurow, Lester C. (New York, 1996)
Stating that America is facing an exciting economic crossroad, a detailed economic analysis cites our nation's trouble spots while charting a course for surviving and maintaining global leadership in the years to come. 100,000 first printing.
Keywords: Economic forecasting,Capitalism,Technological innovations,Chủ nghĩa tư bản,Đổi mới công nghệ; Forecasting,Economic aspects,Forecasting,Dự báo,Khía cạnh kinh tế,Dự báo